Bagaza Virus in Partridges and Pheasants, Spain, 2010 - Montserrat Agüero (Emerging Infectious Diseases, 2011)
In September 2010, an unusually high number of wild birds (partridges and pheasants) died in Cádiz in southwestern Spain. Reverse transcription PCR and virus isolation detected flavivirus infections. Complete nucleotide sequence analysis identified Bagaza virus, a flavivirus with a known distribution that includes sub-Saharan Africa and India, as the causative agent.